Maintenance of Quality of Life Improvements in Diverse Rural Older Adults - Scogin, Forrest (2011)
The maintenance of effects from home-delivered cognitive-behavioral therapy (CBT) was examined. One hundred thirty-four participants, predominantly African American and primarily rural, low-resource, and physically frail, were randomly assigned to either immediate or delayed CBT. The six-month follow-up assessments indicated that among those who remained in the study, participants evidenced significantly improved quality of life and reductions in psychological symptoms at follow-up, relative to pretreatment levels. Posttreatment gains were maintained at follow-up. These data suggest that treatment effects can be achieved and perhaps maintained with a disadvantaged sample of older adults and suggest that evidence-based treatments delivered through nontraditional means can have effects beyond posttreatment.